A simple Markov chain for the extended Collatz problem - Aicardi, Michele (IJRDO -Journal of Computer Science Engineering, 2016)
The paper deals with the Collatz problem. A simple extension of the classic 3n + 1 version is considered allowing the definition of the algorithm for any target base. Then a simple three ”states” Markov chain is built up to show the probabilistic convergence of the algorithm to the equilibrium point.